2020
DOI: 10.2147/cmar.s267345
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-802 Suppresses Tumorigenesis of Colorectal Cancer via Regulating UBN2</p>

Abstract: Background: The initiation and progression of colorectal cancer (CRC) are a multistep complex process regulated by multiple factors. Previous evidence indicated that microRNA-802 (miR-802) participated in tumorigenesis of numerous solid cancers; however, the potential roles and underlying mechanisms of miR-802 in CRC still need further exploration. Methods: Quantitative real-time PCR (qRT-PCR) was employed to evaluate miR-802 levels in human CRC tissues and cell lines. In vitro proliferation, apoptosis, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
“…Subsequent experiments further revealed that miR-802 expression can regulate a series of cell behaviors, including cell proliferatio n, 2,[7][8][9]11,[13][14][15]18,[20][21][22][24][25][26]28,29,31,[33][34][35] invasion, 4,6,[11][12][13][14]17,[19][20][21]33,34,36 metastasis, 2,6,7,[11][12][13][14]17,20,21,25,26,33,34,36 apoptosis, [8][9][10]13,...…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
See 3 more Smart Citations